How low does the oxygen concentration go within a sandwich-type amperometric biosensor? - Romero, Marcelo Ricardo (2012)
Software for the automatic non-linear least squares fit of chronoamperometric responses corresponding to sandwich-type amperometric biosensors has been developed. The so-called Simplex algorithm computes a minimum value for the difference between experimental and theoretical data. The latter consider a numerical model based on a ping-pong reaction mechanism corresponding to an oxidase enzyme that has been immobilized between diffusion membranes. The results obtained from the simulation of a first-generation lactate biosensor in presence of 0.1 mM substrate indicate that the concentration of O 2 would decrease only 0.1% with regards to its bulk value. Besides, the concentration of this natural mediator would remain practically unchanged during a typical calibration curve. This is because the rather high diffusion coefficient of O 2 and its regeneration at the electrode surface minimize the concentration changes of this species. In addition, it was found that the thicknesses of polycarbonate membranes and the enzymatic matrix have average values of 13 μm and 20 μm, respectively. However, these membranes might exhibit smaller thickness depending on the time provided for the crosslinking reaction. In this regard, if this reaction is slow enough, the enzymatic matrix would be able to diffuse through the pores of polycarbonate membranes and they will appear to be thinner than expected. This effect may compromise the response-time and the reproducibility of this kind of biosensors.